Breast cancer among shift workers: results of the WOLF longitudinal cohort study - Knutsson, Anders; Alfredsson, Lars; Karlsson, Berndt; Åkerstedt, Torbjörn; Fransson, Eleonor I; Westerholm, Peter; Westerlund, Hugo (Scandinavian Journal of Work, Environment & Health, 2013)
' ' OBJECTIVE ': 'The aim of this study was to investigate whether shift work (with or without night work) is associated with increased risk of breast cancer. ' ' METHODS ': 'The population consisted of 4036 women. Data were obtained from WOLF (Work, Lipids, and Fibrinogen), a longitudinal cohort study. Information about baseline characteristics was based on questionnaire responses and medical examination. Cancer incidence from baseline to follow-up was obtained from the national cancer registry. Two exposure groups were identified: shift work with and without night work. The group with day work only was used as the reference group in the analysis. Cox regression analysis was used to calculate relative risk. ' ' RESULTS ': 'In total, 94 women developed breast cancer during follow-up. The average follow-up time was 12.4 years. The hazard ratio for breast cancer was 1.23 [95% confidence interval (95% CI) 0.70–2.17] for shifts without night work and 2.02 (95% CI 1.03–3.95) for shifts with night work. When including only women <60 years of age, the risk estimates were 1.18 (95% CI 0.67–2.07) for shifts without night work, and 2.15 (95% CI 1.10–4.21) for shifts with night work. ' ' CONCLUSIONS ': 'Our results indicate an increased risk for breast cancer among women who work shifts that includes night work.
Keywords: breast cancer; cancer; chronodisruption; circadian rhythm; cohort study; Cox regression; melatonin; neoplasm; night work; shift work; shift worker; WOLF